Is it safe to irradiate the newest generation of ventricular assist devices? A case report and systematic literature review. Issue 5 (15th January 2020) - Spano, Giancarlo; Stutz, Emanuel; Elicin, Olgun; Hugi, Beate; Henzen, Dominik; Fürholz, Monika; Wieser, Monika; Rhyner, Daniel; Dobner, Stephan; Pavlicek‐Bahlo, Maryam; Robson, Desiree; Nadel, James; et al.
Abstract: An increasing number of mechanical assist devices, especially left ventricular assist devices (VADs), are being implanted for prolonged periods and as destination therapy. Some VAD patients require radiotherapy due to concomitant oncologic morbidities, including thoracic malignancies. This raises the potential of VAD malfunction via radiation‐induced damage. So far, only case reports and small case series on radiotherapy have been published, most of them on HeartMate II (HMII, Abbott, North Chicago, IL, USA). Significantly, the effects of irradiation on the HeartMate 3 (HM3, Abbott) remain undefined, despite the presence of controller components engineered within the pump itself. We report the first case of a patient with a HM3 who successfully underwent stereotactic hypofractionated radiotherapy due to an early‐stage non‐small‐cell lung cancer. The patient did not suffer from any complications, including toxicity or VAD malfunction. Based on this case report and on published literature, we think that performing radiotherapy after VAD implantation with the aid of a multidisciplinary team could be performed, but more in vitro studies and cases series are needed to reinforce this statement.